(untitled) (Biological Sciences - PJSIR, 1999)
Bulk copolymerization of acrylamide and crotonicacid hasbeencarriedout.The results indicate that both monomers formcopolymerinallmonomericratios.Theinductionperiodis40minutes.Theincreasingconcentrationofacrylamide and benzoyl peroxide and increase in temperature and time enhance the rate of formation of copolymer. Monomer reactivity ratiosofacrylamideandcrotonicacidaredeterminedexperimentallyusingtherearrangedformofcopolymer composition equation. Molecular weightof thecopolymer samplesshowthat the copolymer of low molecular weight maybepreparedathightemperature. Allcopolymersamplesarewhitecrystallinesubstancesthatbecome lightbrown at 200-21ooe and burn when temperature reaches to 270°C.